Soft magnetic powder, and its preparation method and use

By treating magnetic powders with silane coupling and silicon nitriding to form a -Si-N- chemical bond film, the method addresses insulation and density issues, enhancing magnetic performance and reducing losses in soft magnetic powders for high-frequency applications.

JP7603811B2Active Publication Date: 2024-12-20HENGDIAN GRP DMEGC MAGNETICS CO LTD
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
JP2023529050
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2020-12-09
Filing Date
2021-04-21
Publication Date
2024-12-20
Estimated Expiration
2041-04-21

AI Technical Summary

Technical Problem

Existing soft magnetic powders face challenges in achieving high magnetic permeability, low magnetic core loss, and high frequency performance due to issues with insulation and density, with existing coatings failing to provide adequate insulation resistance and stability under high pressures and temperatures.

Method used

A method involving surface silane coupling and silicon nitriding treatment of magnetic powders with different particle sizes, forming a -Si-N- chemical bond compound film to enhance insulation resistance and density, allowing for high deposition density and ultra-high insulation resistance.

Benefits of technology

The method results in improved magnetic flux density, magnetic permeability, and reduced hysteresis and eddy current losses, achieving high initial permeability and low magnetic core loss under large currents and high frequencies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007603811000001
    Figure 0007603811000001
Patent Text Reader

Abstract

The present invention discloses soft magnetic powders, and methods for preparing and using the same. [Solution] The preparation method includes: (1) independently subjecting a first magnetic powder, a second magnetic powder, and a third magnetic powder to surface silane coupling and silicon nitriding treatment to obtain the first magnetic powder, the second magnetic powder, and the third magnetic powder, each of which has a surface coated with a compound film of -Si-N- chemical bonding; and (2) mixing the first magnetic powder, the second magnetic powder, and the third magnetic powder, each of which has a surface coated with a compound film of -Si-N- chemical bonding, to obtain a soft magnetic powder.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present application is in the field of magnetic materials and relates to soft magnetic powders, as well as their preparation and use. [Background technology]

[0002] With the progress of electronic technology and the trend of market development, inductance assemblies are developed toward higher frequency, smaller size and lower power consumption.

[0003] A typical application of soft magnetic powder includes magnetic core members. The magnetic core members are magnetic material members having high magnetic permeability for limiting and guiding inductors such as reactors, transformers, and choke coils used in electric devices, electromechanical devices, and magnetic devices, such as boost circuits, power generation / transformation equipment. The dust magnetic core used here may be prepared from a soft magnetic powder mixture containing a soft magnetic material and an adhesive material. Then, such a mixture containing magnetic powder and an adhesive material is formed into a magnetic body or magnetic core by a press molding process. It is required that an inductor having such a dust core has high magnetic permeability, low iron loss, and excellent DC superposition characteristics.

[0004] In general, in electronic applications, and particularly in alternating current (AC) applications, the two main characteristics of a magnetic core member are its magnetic permeability and magnetic core loss characteristics. Meanwhile, the magnetic permeability of a material provides a measure of the material's ability to be magnetized or to carry magnetic flux. Magnetic permeability is defined as the ratio of the induced magnetic flux to the magnetizing force or magnetic field strength. When a magnetic material is exposed to a rapidly changing magnetic field, the total energy of the core is reduced due to the occurrence of hysteresis losses and / or eddy current losses. Hysteresis losses cause the required energy dissipation to exceed the magnetic force retained within the core member. Eddy current losses cause currents (due to the flux of magnetic flux induced by AC conditions) to be generated in the core member, and are essentially resistive losses.

[0005] Typically, inductance for high frequency applications is sensitive to magnetic core losses, and it is necessary to improve the insulation properties to reduce losses due to eddy currents. The simplest means to achieve this goal is to thicken the insulation layer of each particle. However, the thicker the insulation layer, the lower the core density of the soft magnetic particles, resulting in a lower magnetic flux density (and correspondingly lower magnetic permeability). Also, attempts to increase the magnetic flux density by compaction under high pressure may induce large stresses in the core, resulting in high hysteresis losses.

[0006] Therefore, in order to produce soft magnetic powder cores with optimal core characteristics, it is necessary to simultaneously increase the resistivity and density of the cores. This makes it desirable for the particles to be covered with a thin insulating layer with high insulating properties. In the field of magnetic powders, there are different routes to solve this problem.

[0007] CN103415899B discloses a phosphoric acid-based conversion coating formed on the surface of an iron-based soft magnetic powder for dust magnetic cores, and a silicone resin coating formed on the surface of this coating. By forming an insulating coating by coating the powder with the above-mentioned phosphoric acid-based resin and silicone resin, the insulation resistance and thermal stability of the powder are improved, and the eddy current loss is reduced.

[0008] JP2009120915A discloses an example of coating a metallic magnetic material with an inorganic coating layer (phosphate).

[0009] The phosphates described in the two documents mentioned above have low toughness, so that the coating film is damaged when the molding pressure is increased, and is not stable at annealing temperatures above 650°C, and may significantly increase eddy current loss and deteriorate inductance performance.

[0010] JP2010251437A discloses a method for applying magnetic powder in which the coating layer contains magnesium fluoride (MgF2) to improve the insulation on the surface of the magnetic powder and reduce eddy current loss. The magnesium fluoride (MgF2) in this document has poor thermal stability and is not suitable for annealing processes at 650°C or higher.

[0011] US20080117008A1 discloses a magnetic body including a magnetic powder coated with an oxide binder and an insulating film, in which the insulating film is present between the magnetic powder and the oxide binder. The oxide binder includes a glassy oxide such as silica. The glassy oxide such as silica in this document is mechanically bonded to the magnetic powder, and is in a discrete state, not uniformly distributed, and prone to peeling off and falling off from the magnetic powder under high pressure molding conditions, which greatly affects the effectiveness of the insulating coating.

[0012] CN102543350A discloses a preparation method for achieving the effect of high magnetic flux density by mixing an iron-based soft magnetic powder with a lubricant such as polyhydroxycarboxylic acid amide to prepare a mixture, and then compressing the mixture to obtain a green compact. Although a high press density (high magnetic flux density) can be achieved by optimizing the lubricant system, the performance of high frequency, low loss, and high magnetic permeability required after miniaturization of conventional inductance cannot be met, so it is necessary to further improve the magnetic flux density.

[0013] Therefore, how to provide a mixed magnetic powder for manufacturing inductance electronic components, particularly a mixed magnetic powder that has high permeability and low loss at high frequencies and is applicable at high frequencies, is currently a technical problem that needs to be solved. Summary of the Invention [Problem to be solved by the invention]

[0014] The present application aims to provide a soft magnetic powder, and its preparation method and use. In the present application, by combining and depositing three kinds of magnetic powders with different particle sizes and types, which are surface-silane-coupling and silicon-nitriding-treated, the effects of high deposition density and ultra-high insulation resistance can be achieved under normal pressing pressure. [Means for solving the problem]

[0015] To achieve this objective, the present application provides the following technical solutions.

[0016] In a first aspect, the present application provides a method for producing a method for manufacturing a semiconductor device comprising: (1) subjecting the first magnetic powder, the second magnetic powder and the third magnetic powder to surface silane coupling and silicon nitriding treatment independently to obtain the first magnetic powder having a surface coated with a -Si-N- chemically bonded compound film, the second magnetic powder having a surface coated with a -Si-N- chemically bonded compound film, and the third magnetic powder having a surface coated with a -Si-N- chemically bonded compound film; and (2) mixing a first magnetic powder having a surface coated with a -Si-N-chemically bonded compound film, a second magnetic powder having a surface coated with a -Si-N-chemically bonded compound film, and a third magnetic powder having a surface coated with a -Si-N-chemically bonded compound film to obtain a soft magnetic powder.

[0017] In the above preparation method, the first magnetic powder, the second magnetic powder and the third magnetic powder are each independently subjected to surface silane coupling and silicon nitriding treatment, and these two treatments exert a synergistic effect to form a dense compound film containing -Si-N- chemical bonds with a certain thickness on the surface of the soft magnetic powder, so that the soft magnetic powder can achieve the effects of high deposition density and ultra-high insulation resistance under normal pressing pressure.

[0018] At the same time, a dense thin film cannot be formed by surface silane coupling alone. A single silane coupling agent forms silanol after hydrolysis, which has poor binding strength with the surface of the metal-based soft magnetic powder, and is only a general physical bond or hydrogen bond, and cannot achieve good organic bonding. Therefore, in the process of pressing the powder into the magnetic core, it is easy to peel off, and the corresponding insulating and protective functions are not achieved.

[0019] Preferably, the surface silane coupling treatment in step (1) includes independently immersing the first magnetic powder, the second magnetic powder and the third magnetic powder in a silane coupling agent-acetone solution.

[0020] In the present application, the silane coupling agent-acetone solution refers to a solution obtained by mixing a silane coupling agent and acetone, where the silane coupling agent may be selected from KH550, KH540, KH560, KH792 or KH793, and is preferably KH550.

[0021] Preferably, the concentration of the silane coupling agent-acetone solution is 5 to 15 wt%, for example, 5 wt%, 6 wt%, 7 wt%, 8 wt%, 9 wt%, 10 wt%, 12 wt%, or 15 wt%.

[0022] Preferably, the amount of silane coupling agent added in the silane coupling agent-acetone solution in which the first magnetic powder is immersed is 0.3 to 1 wt% of the weight of the first magnetic powder, for example 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt% or 1 wt%.

[0023] Preferably, the amount of silane coupling agent added in the silane coupling agent-acetone solution in which the second magnetic powder is immersed is 0.6 to 1.2 wt% of the weight of the second magnetic powder, for example 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 1.1 wt% or 1.2 wt%.

[0024] Preferably, the amount of silane coupling agent added in the silane coupling agent-acetone solution in which the third magnetic powder is immersed is 1 to 2 wt% of the weight of the third magnetic powder, for example, 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt% or 2 wt%.

[0025] The amount of silane coupling agent added in the silane coupling agent-acetone solution is determined by the average particle size of the magnetic powder. The coarser the magnetic powder, the lower the amount of silane coupling agent required. This is mainly related to the small specific surface area of ​​the coarse powder, and the finer the powder, the larger the specific surface area and the higher the amount of silane coupling agent required.

[0026] Preferably, the silane coupling treatment in step (1) further includes stirring the first magnetic powder, the second magnetic powder and the third magnetic powder after the immersion and allowing them to volatilize naturally until the solution is removed.

[0027] Preferably, the silicon nitriding treatment in step (1) includes annealing the first magnetic powder, the second magnetic powder and the third magnetic powder after the silane coupling treatment in a tubular annealing furnace, respectively.

[0028] Preferably, the gas atmosphere in the annealing treatment contains nitrogen gas or a mixture of nitrogen gas and ammonia gas.

[0029] The magnetic powder is surface-treated with a silane coupling agent and then annealed. Compared with the case where annealing is not performed after normal coupling, when annealing is performed, a dense -Si-N-based compound thin film layer can be formed, which significantly improves the insulation of the powder and the insulation of the pressed magnetic core (the corresponding magnetic core loss is significantly reduced). Furthermore, the atmospheric gas used for annealing includes a nitrogen gas-ammonia gas mixture or nitrogen gas, but atmospheres such as hydrogen gas, air, oxygen gas, and argon gas cannot be used. This is mainly because if an atmosphere such as hydrogen gas, air, oxygen gas, and argon gas is used, a dense -Si-N-based compound thin film layer cannot be formed and the insulating effect cannot be achieved. However, after the magnetic powder in the present application is surface-treated with a silane coupling agent, a silicon-containing thin film is formed on the surface, and a dense -Si-N-based compound thin film layer can be formed by annealing with a nitrogen gas-ammonia gas mixture or nitrogen gas, etc., and in particular, the temperature resistance and insulation properties of the -Si-N-based compound are both excellent. However, in an atmosphere of hydrogen gas, air, oxygen gas, argon gas, or the like, it is not possible to form a thin film layer having excellent temperature resistance and insulating properties.

[0030] Preferably, the annealing temperature in the annealing treatment is 350 to 550°C, for example, 350°C, 380°C, 400°C, 430°C, 450°C, 480°C, 500°C, 530°C, or 550°C.

[0031] Preferably, the total gas flow rate in the annealing treatment is 0.2 to 1 L / min, for example, 0.2 L / min, 0.3 L / min, 0.4 L / min, 0.5 L / min, 0.6 L / min, 0.7 L / min, 0.8 L / min, 0.9 L / min or 1 L / min.

[0032] Preferably, the annealing time in the annealing treatment is 1 to 5 hours, such as 1 hour, 2 hours, 3 hours, 4 hours or 5 hours.

[0033] Preferably, the mixing in step (2) includes mixing the first magnetic powder having a surface coated with a -Si-N-chemically bonded compound film obtained in step (1), the second magnetic powder having a surface coated with a -Si-N-chemically bonded compound film, and the third magnetic powder having a surface coated with a -Si-N-chemically bonded compound film in a three-dimensional mixer.

[0034] Preferably, the time of mixing in step (2) is 1 to 2 h, such as 1.1 h, 1.2 h, 1.3 h, 1.4 h, 1.5 h, 1.6 h, 1.7 h, 1.8 h, 1.9 h or 2 h.

[0035] As a preferred technical solution, the method for preparing the soft magnetic material includes: The first magnetic powder is immersed in a silane coupling agent-acetone solution having a concentration of 5 to 15 wt%, the amount of the silane coupling agent added being 0.3 to 1.0 wt% of the weight of the first magnetic powder, and the solution is naturally evaporated while stirring until it is removed; The second magnetic powder is immersed in a silane coupling agent-acetone solution having a concentration of 5 to 15 wt%, the amount of the silane coupling agent added being 0.6 to 1.2 wt% of the weight of the second magnetic powder, and the solution is naturally evaporated while stirring until it is removed; The third magnetic powder is immersed in a silane coupling agent-acetone solution having a concentration of 5 to 15 wt%, the amount of the silane coupling agent added being 1 to 2 wt% of the weight of the third magnetic powder, and the solution is naturally evaporated while stirring until it is removed; The first magnetic powder, the second magnetic powder, and the third magnetic powder after the silane coupling treatment are each independently annealed in a tubular annealing furnace under a mixed atmosphere of nitrogen gas and ammonia gas at an annealing temperature of 350 to 550°C for 1 to 5 hours to obtain the first magnetic powder coated with a -Si-N- chemical bond compound film on its surface, the second magnetic powder coated with a -Si-N- chemical bond compound film on its surface, and the third magnetic powder coated with a -Si-N- chemical bond compound film on its surface (wherein the total flow rate during the annealing process is 0.2 to 1 L / min); and step (2) of placing the first magnetic powder having a surface coated with a -Si-N- chemical bond compound film in step (1), the second magnetic powder having a surface coated with a -Si-N- chemical bond compound film, and the third magnetic powder having a surface coated with a -Si-N- chemical bond compound film in a three-dimensional mixer and mixing for 1 to 2 hours to obtain a soft magnetic powder.

[0036] In a second aspect, the present application provides a soft magnetic powder prepared by the method for preparing a soft magnetic powder described in the first aspect, the soft magnetic powder comprising a first magnetic powder, a second magnetic powder and a third magnetic powder, the surfaces of each of the first magnetic powder, the second magnetic powder and the third magnetic powder being coated with a single layer of a compound film, and the compound in the compound film containing a -Si-N- chemical bond.

[0037] In the present application, the compound film containing -Si-N- chemical bonds on the surfaces of the first magnetic powder, the second magnetic powder and the third magnetic powder among the soft magnetic powders can adhere to the surface of the magnetic powders and act as a surface insulation, thereby improving the insulation resistance of the soft magnetic powder; further, by combining and depositing three types of magnetic powders, the magnetic flux density, magnetic permeability and superposition performance under large current of the soft magnetic powder can be improved, and the hysteresis loss can be significantly reduced.

[0038] Preferably, the first magnetic powder contains any one or a combination of at least two of an Fe-Si-Al based alloy, an Fe-Ni based alloy, an Fe-Si based alloy, an Fe-Si-Cr based alloy, or an Fe-Si-Ni based alloy.

[0039] Preferably, the weight ratio of the first magnetic powder in the soft magnetic powder is 50 to 90%, for example, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85% or 90%.

[0040] Preferably, the D50 of the first magnetic powder is 15 to 45 μm, for example 15 μm, 20 μm, 25 μm, 30 μm, 35 μm, 40 μm or 45 μm, and is preferably 21 to 30 μm.

[0041] The first magnetic powder having a median diameter in the above range has good magnetic permeability and relatively low magnetic core loss performance when applied under high frequency conditions.

[0042] Preferably, the second magnetic powder includes one or a combination of at least two of an Fe-Si-Al based alloy, an Fe-Ni based alloy, an Fe-Si based alloy, an Fe-Si-Cr based alloy, an Fe-Si-Ni based alloy, and carbonyl iron powder.

[0043] Preferably, the weight ratio of the second magnetic powder in the soft magnetic powder is 10 to 40%, for example 10%, 15%, 20%, 25%, 30%, 35% or 40%.

[0044] Preferably, the D50 of the second magnetic powder is 2 to 10 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm or 10 μm, and preferably 4 to 7 μm.

[0045] The second magnetic powder having a median diameter in the above range can be combined and stacked with the first magnetic powder at an effective particle size, thereby obtaining good magnetic permeability and magnetic core loss performance when applied under high frequency conditions.

[0046] Preferably, the third magnetic powder contains one or a combination of at least two of an Fe-Si-B based amorphous alloy, an Fe-Si-Cr-B based amorphous alloy, and an amorphous carbonyl iron powder.

[0047] Preferably, the weight ratio of the third magnetic powder in the soft magnetic powder is 5 to 15%, for example 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%.

[0048] Preferably, the D50 of the third magnetic powder is 2 to 8 μm, for example, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm or 8 μm, and is preferably 3 to 7 μm.

[0049] The third magnetic powder having a median diameter in the above range can be combined and stacked with the first magnetic powder at an effective particle size, thereby obtaining good magnetic permeability and magnetic core loss performance when applied under high frequency conditions.

[0050] Preferably, the thickness of the compound film on the surface of the first magnetic powder is 20 to 100 nm, for example, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 85 nm, 90 nm, 95 nm or 100 nm, and preferably 30 to 70 nm.

[0051] Preferably, the thickness of the compound film on the surface of the second magnetic powder is 10 to 40 nm, for example 10 nm, 15 nm, 20 nm, 25 nm, 30 nm, 35 nm or 40 nm, and preferably 15 to 25 nm.

[0052] Preferably, the thickness of the compound film on the surface of the third magnetic powder is 20 to 70 nm, for example, 20 nm, 25 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm or 70 nm, and preferably 30 to 50 nm.

[0053] The thicker the compound film containing -Si-N- chemical bonds, the higher the insulation resistance of the powder and the lower the eddy current loss at high frequencies. However, since this usually significantly reduces the initial permeability and improves the hysteresis loss, the thickness of the surface insulation coating of the first magnetic powder, the second magnetic powder and the third magnetic powder is very important for high frequency applications.

[0054] As a third aspect, the present application further provides a magnetic powder core prepared by the soft magnetic powder described in the second aspect. Effect of the Invention

[0055] Compared with the prior art, the present application has the following beneficial effects:

[0056] The present invention combines and deposits magnetic powders with different magnetic properties and different particle size distributions, and then performs surface silane coupling and silicon nitriding treatment on the magnetic powder to form a dense compound film containing -Si-N- chemical bonds on the surface, thereby achieving good insulation and improving the insulation resistance of the soft magnetic powder, and making the soft magnetic powder achieve high deposition density (with corresponding improvements in magnetic flux density, magnetic permeability, and superposition performance under large current, and reduction in hysteresis loss) and ultra-high insulation resistance (with corresponding eddy current loss, especially eddy current loss under high frequency, obviously reduced). Its initial permeability can reach 72.3 or more, while the magnetic core loss can be reduced to 3795@1M*50mT. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0057] The following further describes the technical solution of the present application based on specific examples. Those skilled in the art should understand that the above examples are only for understanding the present application, and should not be considered as specifically limiting the present application.

[0058] The silane coupling agent used in the following examples and comparative examples is KH550.

[0059] Example 1

[0060] This embodiment provides a soft magnetic powder including Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder, and the surfaces of the Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder are all coated with a layer of a compound film, and the compound in the compound film contains -Si-N- chemical bonds.

[0061] the thickness of the compound film on the surface of the Fe-Si-Al powder is 48 nm; The thickness of the compound film on the surface of the Fe-Ni powder is 22 nm; The compound film on the surface of the carbonyl iron powder amorphous powder has a thickness of 38 nm.

[0062] The method for preparing the soft magnetic powder includes the steps of: The Fe-Si-Al powder having a median diameter of 25.6 μm was immersed in a silane coupling agent-acetone solution having a concentration of 10 wt%, and the amount of the silane coupling agent added was 0.7 wt% of the weight of the Fe-Si-Al powder. The solution was allowed to evaporate naturally while stirring until it was removed. Fe-Ni powder with a median diameter of 5.8 μm was immersed in a silane coupling agent-acetone solution with a concentration of 13 wt%, and the amount of the silane coupling agent added was 1 wt% of the weight of the Fe-Ni powder. The solution was allowed to evaporate naturally while stirring until it was removed. A carbonyl iron powder amorphous powder with a median diameter of 4.5 μm is immersed in a silane coupling agent-acetone solution with a concentration of 15 wt%, the amount of the silane coupling agent added is 1.5 wt% of the weight of the carbonyl iron powder amorphous powder, and the solution is naturally evaporated while stirring until it is removed. The Fe-Si-Al powder after the silane coupling treatment was annealed in a tubular annealing furnace at 380°C for 3 hours under a nitrogen gas atmosphere with a total flow rate of 0.6 L / min. The Fe-Ni powder after the silane coupling treatment was annealed in a tubular annealing furnace at 420°C for 3 hours under a nitrogen gas atmosphere with a total flow rate of 0.6 L / min. The carbonyl iron powder amorphous powder after the silane coupling treatment was annealed in a tubular annealing furnace at 420°C for 3 hours in a nitrogen gas atmosphere with a total flow rate of 0.6 L / min. (1) obtaining Fe-Si-Al powder having a surface coated with a -Si-N- chemical bond compound film, Fe-Ni powder having a surface coated with a -Si-N- chemical bond compound film, and carbonyl iron powder amorphous powder having a surface coated with a -Si-N- chemical bond compound film; and step (2) of placing the Fe-Si-Al powder having a -Si-N chemical bond compound film on its surface, the Fe-Ni powder having a -Si-N chemical bond compound film on its surface, and the carbonyl iron powder amorphous powder having a -Si-N chemical bond compound film on its surface coated thereon in a three-dimensional mixer in a mixing ratio of 70:22:8 in step (1), and mixing the powder uniformly for 2 hours to obtain the soft magnetic powder.

[0063] Example 2

[0064] This embodiment provides a soft magnetic powder including Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder, and the surfaces of the Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder are all coated with a layer of a compound film, and the compound in the compound film contains -Si-N- chemical bonds.

[0065] the thickness of the compound film on the surface of the Fe-Si-Al powder is 20 nm; The thickness of the compound film on the surface of the Fe-Ni powder is 22 nm; The compound film on the surface of the carbonyl iron powder amorphous powder has a thickness of 38 nm.

[0066] The difference between this embodiment and Example 1 is that the median diameter of the Fe-Si-Al powder is 21 μm, the median diameter of the Fe-Ni powder is 4 μm, and the median diameter of the carbonyl iron powder amorphous powder is 4 μm. The other preparation methods and parameters are consistent with those of Example 1.

[0067] Example 3

[0068] This embodiment provides a soft magnetic powder including Fe-Ni powder, carbonyl iron powder, and Fe-Si-B powder, in which the surfaces of the Fe-Ni powder, carbonyl iron powder, and Fe-Si-B powder are all coated with a layer of a compound film, and the compound in the compound film contains a -Si-N- chemical bond.

[0069] the thickness of the compound film on the surface of the Fe-Ni powder is 100 nm; the thickness of the compound film on the surface of the carbonyl iron powder is 10 nm; The thickness of the compound film on the surface of the Fe-Si-B powder is 70 nm.

[0070] The method for preparing the soft magnetic powder includes the steps of: Fe-Ni powder with a median diameter of 45 μm was immersed in a silane coupling agent-acetone solution with a concentration of 5 wt%, and the amount of the silane coupling agent added was 0.9 wt% of the weight of the Fe-Ni powder. The solution was allowed to evaporate naturally while stirring until it was removed. Carbonyl iron powder with a median diameter of 7 μm was immersed in a silane coupling agent-acetone solution with a concentration of 5 wt%, and the amount of the silane coupling agent added was 0.8 wt% of the weight of the carbonyl iron powder. The solution was allowed to evaporate naturally while stirring until it was removed. Fe-Si-B powder with a median diameter of 7 μm is immersed in a silane coupling agent-acetone solution with a concentration of 5 wt%, so that the amount of the silane coupling agent added is 1.8 wt% of the weight of the Fe-Si-B powder, and the solution is naturally evaporated while stirring until it is removed. The Fe-Ni powder after the silane coupling treatment was annealed in a tubular annealing furnace at 350°C for 5 hours in a nitrogen gas atmosphere with a total flow rate of 0.4 L / min. The carbonyl iron powder after the silane coupling treatment was annealed in a tubular annealing furnace at 450°C for 1 hour in a nitrogen gas atmosphere with a total flow rate of 1 L / min. The Fe-Si-B powder after the silane coupling treatment was annealed in a tubular annealing furnace at 420°C for 3 hours under a nitrogen gas atmosphere with a total flow rate of 0.6 L / min. A step (1) of obtaining an Fe-Ni powder having a surface coated with a -Si-N- chemical bond compound film, a carbonyl iron powder having a surface coated with a -Si-N- chemical bond compound film, and an Fe-Si-B powder having a surface coated with a -Si-N- chemical bond compound film; and (2) placing the Fe-Ni powder coated with a -Si-N- chemical bond compound film on its surface, the carbonyl iron powder coated with a -Si-N- chemical bond compound film on its surface, and the Fe-Si-B powder coated with a -Si-N- chemical bond compound film on its surface in step (1) in a mixing ratio of 60:30:10 in a three-dimensional mixer and mixing them uniformly for 1 hour to obtain the soft magnetic powder.

[0071] Example 4

[0072] The present embodiment is different from the first embodiment in that the atmospheric gas in the silicon nitriding process is a mixed gas of nitrogen gas and ammonia gas, while the other preparation methods and parameters are the same as those of the first embodiment.

[0073] Example 5

[0074] This embodiment provides a soft magnetic powder including Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder, and the surfaces of the Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder are all coated with a layer of a compound film, and the compound in the compound film contains -Si-N- chemical bonds.

[0075] the thickness of the compound film on the surface of the Fe-Si-Al powder is 17 nm; The thickness of the compound film on the surface of the Fe-Ni powder is 22 nm; The compound film on the surface of the carbonyl iron powder amorphous powder has a thickness of 38 nm.

[0076] The present embodiment is distinguished from Example 1 in that the median diameter of the Fe-Si-Al powder is 14 μm, while the other preparation methods and parameters are consistent with those of Example 1.

[0077] Example 6

[0078] This embodiment provides a soft magnetic powder including Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder, and the surfaces of the Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder are all coated with a layer of a compound film, and the compound in the compound film contains -Si-N- chemical bonds.

[0079] the thickness of the compound film on the surface of the Fe-Si-Al powder is 110 nm; The thickness of the compound film on the surface of the Fe-Ni powder is 22 nm; The compound film on the surface of the carbonyl iron powder amorphous powder has a thickness of 38 nm.

[0080] The present embodiment is distinguished from Example 1 in that the median diameter of the Fe-Si-Al powder is 46 μm, while the other preparation methods and parameters are consistent with those of Example 1.

[0081] Example 7

[0082] This embodiment provides a soft magnetic powder including Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder, and the surfaces of the Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder are all coated with a layer of a compound film, and the compound in the compound film contains -Si-N- chemical bonds.

[0083] the thickness of the compound film on the surface of the Fe-Si-Al powder is 48 nm; The thickness of the compound film on the surface of the Fe-Ni powder is 22 nm; The compound film on the surface of the carbonyl iron powder amorphous powder has a thickness of 38 nm.

[0084] The present embodiment is distinguished from Example 1 in that the median diameter of the Fe-Ni powder is 2 μm, while the other preparation methods and parameters are consistent with those of Example 1.

[0085] Example 8

[0086] This embodiment provides a soft magnetic powder including Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder, and the surfaces of the Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder are all coated with a layer of a compound film, and the compound in the compound film contains -Si-N- chemical bonds.

[0087] the thickness of the compound film on the surface of the Fe-Si-Al powder is 48 nm; The thickness of the compound film on the surface of the Fe-Ni powder is 22 nm; The compound film on the surface of the carbonyl iron powder amorphous powder has a thickness of 38 nm.

[0088] The present embodiment is distinguished from Example 1 in that the median diameter of the Fe-Ni powder is 10 μm, while the other preparation methods and parameters are consistent with those of Example 1.

[0089] Example 9

[0090] This embodiment provides a soft magnetic powder including Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder, and the surfaces of the Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder are all coated with a layer of a compound film, and the compound in the compound film contains -Si-N- chemical bonds.

[0091] the thickness of the compound film on the surface of the Fe-Si-Al powder is 48 nm; The thickness of the compound film on the surface of the Fe-Ni powder is 7 nm; The compound film on the surface of the carbonyl iron powder amorphous powder has a thickness of 38 nm.

[0092] The difference between this embodiment and Example 1 is that the median diameter of the carbonyl iron powder amorphous powder is 2 μm, and other preparation methods and parameters are the same as those of Example 1.

[0093] Example 10

[0094] This embodiment provides a soft magnetic powder including Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder, and the surfaces of the Fe-Si-Al powder, Fe-Ni powder, and carbonyl iron powder amorphous powder are all coated with a layer of a compound film, and the compound in the compound film contains -Si-N- chemical bonds.

[0095] the thickness of the compound film on the surface of the Fe-Si-Al powder is 48 nm; The thickness of the compound film on the surface of the Fe-Ni powder is 22 nm; The compound film on the surface of the carbonyl iron powder amorphous powder has a thickness of 75 nm.

[0096] The difference between this embodiment and Example 1 is that the median diameter of the carbonyl iron powder amorphous powder is 8 μm, and other preparation methods and parameters are the same as those of Example 1.

[0097] Example 11

[0098] The present embodiment is different from the first embodiment in that the atmospheric gas in the silicon nitriding process is air, while the other preparation methods and parameters are the same as those of the first embodiment.

[0099] Example 12

[0100] The present embodiment is different from the first embodiment in that the atmospheric gas in the silicon nitriding process is hydrogen gas, and other preparation methods and parameters are the same as those of the first embodiment.

[0101] Comparative Example 1

[0102] This comparative example provides a soft magnetic powder containing Fe-Si-Al powder and Fe-Ni powder, and the surfaces of the Fe-Si-Al powder and the Fe-Ni powder are both coated with one layer of a compound film, and the compound in the compound film contains -Si-N- chemical bonds.

[0103] the thickness of the compound film on the surface of the Fe-Si-Al powder is 48 nm; The thickness of the compound film on the surface of the Fe-Ni powder was 22 nm.

[0104] In the preparation method, except that there is no treatment for the carbonyl iron powder amorphous powder, the other preparation processes and parameters are consistent with Example 1.

[0105] Comparative Example 2

[0106] This comparative example provides a soft magnetic powder containing Fe-Si-Al powder and carbonyl iron powder amorphous powder, and the surfaces of the Fe-Si-Al powder and the carbonyl iron powder amorphous powder are both coated with a layer of a compound film, and the compound in the compound film contains -Si-N- chemical bonds.

[0107] the thickness of the compound film on the surface of the Fe-Si-Al powder is 48 nm; The compound film on the surface of the carbonyl iron powder amorphous powder has a thickness of 38 nm.

[0108] In the preparation method, except that there is no treatment on the Fe-Ni powder, the other preparation processes and parameters are consistent with those in Example 1.

[0109] Comparative Example 3

[0110] This comparative example provides a soft magnetic powder containing Fe-Ni powder and carbonyl iron powder amorphous powder, and the surfaces of the Fe-Ni powder and the carbonyl iron powder amorphous powder are both coated with a layer of a compound film, and the compound in the compound film contains -Si-N- chemical bonds.

[0111] The thickness of the compound film on the surface of the Fe-Ni powder is 22 nm; The compound film on the surface of the carbonyl iron powder amorphous powder has a thickness of 38 nm.

[0112] In the preparation method, except that there is no treatment on the Fe-Si-Al powder, the other preparation processes and parameters are consistent with those in Example 1.

[0113] Comparative Example 4

[0114] This comparative example provides soft magnetic powders including Fe-Si-Al powder, Fe-Ni powder and carbonyl iron powder amorphous powder.

[0115] In the preparation method, the Fe-Si-Al powder, Fe-Ni powder and carbonyl iron powder amorphous powder were not subjected to surface silane coupling treatment and silicon nitriding treatment, but the other preparation processes and parameters were the same as those in Example 1.

[0116] Comparative Example 5

[0117] This comparative example provides soft magnetic powders including Fe-Si-Al powder, Fe-Ni powder and carbonyl iron powder amorphous powder.

[0118] In the preparation method, Fe-Si-Al powder, Fe-Ni powder and carbonyl iron powder amorphous powder were not subjected to silicon nitriding treatment, but only surface silane coupling treatment was performed, and the other preparation processes and parameters were the same as those in Example 1.

[0119] Tests were carried out on the soft magnetic powders prepared in Examples 1 to 12 and Comparative Examples 1 to 5. The test methods and processes are as follows.

[0120] 1. The soft magnetic powders in Examples 1-12 and Comparative Examples 1-5 were each placed in a coating device independently, and 1.0 wt% of a silicon organic resin binder (a solution in acetone with a concentration of 10 wt%) was gradually added, and the soft magnetic powder material was prepared into a columnar soft magnetic powder material having a certain degree of roundness in a semi-dried state by a granulator. 2. The soft magnetic powder material was press-molded with a press force of 1500 MPa to obtain a magnetic core of Φ26.92*Φ14.73*11.18. 3. The molded magnetic core was annealed at a temperature of 700°C to remove the press molding stress of the magnetic core, where the atmosphere was nitrogen gas. 4. Test evaluation analysis: For the above annealed magnetic core, the coil winding number is 30, and the initial magnetic permeability μi of the magnetic core is evaluated using the British Wayne Kerr WK3260B precision magnetic element analyzer; the coil winding number is 30*5, and the magnetic core loss at different frequencies and external magnetic fields of the magnetic core is evaluated using the Japanese Iwasaki SY-8218 soft magnetic BH analyzer. In this application, the characteristic values ​​are mainly evaluated under the conditions of high frequency 1M and external magnetic field 50mT.

[0121] Table 1 shows the data results of Examples 1-12 and Comparative Examples 1-5.

[0122] [Table 1]

[0123] As can be seen from the data results of Examples 1 and 5, when the median diameter of the Fe-Si-Al powder is smaller than 15 μm, the thickness of the compound film on the corresponding surface is accordingly reduced to 20 nm or less. In this case, the initial magnetic permeability of Example 5 is smaller than 70.

[0124] As can be seen from the data results of Example 1 and Example 6, when the median diameter of the Fe-Si-Al powder exceeds 45 μm, the thickness of the compound film on the corresponding surface is improved to 100 nm or more. The powder is too coarse, which further aggravates the loss of the magnetic core.

[0125] As can be seen from the data results of Examples 1 and 5 to 10, if the median diameter of any one of the magnetic powders, whether the first magnetic powder, the second magnetic powder, or the third magnetic powder, exceeds or is smaller than the numerical range in the present application, either the initial permeability or loss will change, clearly deteriorating the performance of the magnetic powder core.

[0126] As can be seen from the data results of Examples 1, 11 and 12, by performing annealing treatment in an air or hydrogen gas atmosphere, the magnetic powder was unable to form a dense -Si-N-based compound thin film layer, which resulted in a significant deterioration in the insulating effect, ultimately leading to a worsening of the loss of the magnetic powder core.

[0127] As can be seen from the data results of Example 1 and Comparative Examples 1 to 3, the effect of mixing two types of magnetic powders was worse than the effect of mixing three types of magnetic powders in the present application, so that the magnetic permeability could not be improved or the loss increased. As can be seen from the data results of Example 1 and Comparative Example 4, the insulation of the powder surface was poor and the loss under high frequency conditions was high due to the fact that the magnetic powder was not subjected to surface silane coupling treatment and silicon nitriding treatment.

[0128] As can be seen from the data results of Example 1 and Comparative Example 5, the loss was also clearly high due to the absence of silicon nitriding treatment and the carrying out of only the surface silane coupling treatment.

[0129] Although the above-mentioned specific examples have further explained the objectives, technical solutions and beneficial effects of the present application in detail, it should be understood that the above-mentioned specific examples are merely specific examples of the present application and are not intended to limit the present application.

Claims

1. A step (1) of subjecting the first magnetic powder, the second magnetic powder and the third magnetic powder to a surface silane coupling treatment and a silicon nitriding treatment independently to obtain the first magnetic powder having a surface coated with a -Si-N- chemically bonded compound film, the second magnetic powder having a surface coated with a -Si-N- chemically bonded compound film, and the third magnetic powder having a surface coated with a -Si-N- chemically bonded compound film; (2) mixing a first magnetic powder having a surface coated with a -Si-N- chemically bonded compound film, a second magnetic powder having a surface coated with a -Si-N- chemically bonded compound film, and a third magnetic powder having a surface coated with a -Si-N- chemically bonded compound film to obtain a soft magnetic powder; Including, The surface silane coupling treatment in step (1) includes immersing the first magnetic powder, the second magnetic powder, and the third magnetic powder independently in a silane coupling agent-acetone solution; The silicon nitriding treatment in step (1) includes annealing the first magnetic powder, the second magnetic powder, and the third magnetic powder after the silane coupling treatment in a tubular annealing furnace, respectively; the first magnetic powder contains any one or a combination of at least two of an Fe—Si—Al based alloy, an Fe—Ni based alloy, an Fe—Si based alloy, an Fe—Si—Cr based alloy, or an Fe—Si—Ni based alloy; the second magnetic powder comprises one or a combination of at least two of an Fe—Si—Al alloy, an Fe—Ni alloy, an Fe—Si alloy, an Fe—Si—Cr alloy, an Fe—Si—Ni alloy, and a carbonyl iron powder; the third magnetic powder comprises one or a combination of at least two of an Fe-Si-B amorphous alloy, an Fe-Si-Cr-B amorphous alloy, and an amorphous carbonyl iron powder; The first magnetic powder has a D50 of 15 to 45 μm, the second magnetic powder has a D50 of 2 to 10 μm, and the third magnetic powder has a D50 of 2 to 8 μm. Method for preparing soft magnetic powder.

2. The concentration of the silane coupling agent-acetone solution is 5 to 15 wt %; A method for preparing the soft magnetic powder according to claim 1.

3. an amount of the silane coupling agent added in the silane coupling agent-acetone solution in which the first magnetic powder is immersed is 0.3 to 1 wt % of the weight of the first magnetic powder; an amount of the silane coupling agent in the silane coupling agent-acetone solution in which the second magnetic powder is immersed is 0.6 to 1.2 wt % of the weight of the second magnetic powder; an amount of the silane coupling agent added in the silane coupling agent-acetone solution in which the third magnetic powder is immersed is 1 to 2 wt % of the weight of the third magnetic powder; The silane coupling treatment in step (1) further includes stirring the first magnetic powder, the second magnetic powder, and the third magnetic powder after the immersion to allow them to volatilize naturally until the solution is removed. A method for preparing the soft magnetic powder according to claim 1 or 2.

4. A method for preparing a soft magnetic powder described in any one of claims 1 to 3, wherein the atmospheric gas in the annealing treatment contains a mixed gas of nitrogen gas and ammonia gas or nitrogen gas.

5. The annealing temperature in the annealing treatment is 350 to 550°C, The total flow rate of the gas in the annealing treatment is 0.2 to 1 L / min; The annealing time in the annealing treatment is 1 to 5 h; A method for preparing the soft magnetic powder according to any one of claims 1 to 4.

6. The mixing in step (2) includes mixing the first magnetic powder having a surface coated with a -Si-N- chemical bond compound film in step (1), the second magnetic powder having a surface coated with a -Si-N- chemical bond compound film, and the third magnetic powder having a surface coated with a -Si-N- chemical bond compound film in a three-dimensional mixer; The mixing time in step (2) is 1 to 2 h; A method for preparing the soft magnetic powder according to any one of claims 1 to 5.

7. The preparation method comprises the steps of: The first magnetic powder is immersed in a silane coupling agent-acetone solution having a concentration of 5 to 15 wt %, the amount of the silane coupling agent added being 0.3 to 1.0 wt % of the weight of the first magnetic powder, and the solution is naturally evaporated while stirring until it is removed; The second magnetic powder is immersed in a silane coupling agent-acetone solution having a concentration of 5 to 15 wt %, the amount of the silane coupling agent added being 0.6 to 1.2 wt % of the weight of the second magnetic powder, and the solution is naturally evaporated while stirring until it is removed; The third magnetic powder is immersed in a silane coupling agent-acetone solution having a concentration of 5 to 15 wt %, the amount of the silane coupling agent added being 1 to 2 wt % of the weight of the third magnetic powder, and the solution is naturally evaporated while stirring until it is removed; The first magnetic powder, the second magnetic powder and the third magnetic powder after the silane coupling treatment are each independently annealed in a tubular annealing furnace under a mixed atmosphere of nitrogen gas-ammonia gas at an annealing temperature of 350 to 550 ° C. for 1 to 5 h to obtain a first magnetic powder coated with a compound film of -Si-N- chemical bond on its surface, a second magnetic powder coated with a compound film of -Si-N- chemical bond on its surface and a third magnetic powder coated with a compound film of -Si-N- chemical bond on its surface (1) (wherein the total flow rate during the annealing process is 0.2 to 1 L / min); Step (2) of putting the first magnetic powder having a surface coated with a -Si-N- chemical bond compound film in step (1), the second magnetic powder having a surface coated with a -Si-N- chemical bond compound film, and the third magnetic powder having a surface coated with a -Si-N- chemical bond compound film in a three-dimensional mixer and mixing for 1 to 2 hours to obtain a soft magnetic powder; A method for preparing the soft magnetic powder according to any one of claims 1 to 6, comprising:

8. A soft magnetic powder prepared by the method for preparing a soft magnetic powder according to any one of claims 1 to 7, A magnetic material according to claim 1, further comprising a first magnetic powder, a second magnetic powder and a third magnetic powder, The surfaces of the first magnetic powder, the second magnetic powder and the third magnetic powder are all coated with one layer of a compound film, and the compound in the compound film contains --Si--N-- chemical bonds.

9. The weight ratio of the first magnetic powder in the soft magnetic powder is 50 to 90%, The first magnetic powder has a D50 of 21 to 30 μm. The soft magnetic powder according to claim 8.

10. The weight ratio of the second magnetic powder in the soft magnetic powder is 10 to 40%, The second magnetic powder has a D50 of 4 to 7 μm. The soft magnetic powder according to claim 8 or 9.

11. The weight ratio of the third magnetic powder in the soft magnetic powder is 5 to 15%, The third magnetic powder has a D50 of 3 to 7 μm. The soft magnetic powder according to any one of claims 8 to 10.

12. the compound film on the surface of the first magnetic powder has a thickness of 20 to 100 nm; the compound film on the surface of the second magnetic powder has a thickness of 10 to 40 nm; the compound film on the surface of the third magnetic powder has a thickness of 20 to 70 nm; The soft magnetic powder according to any one of claims 8 to 11.

13. A magnetic powder core prepared from the soft magnetic powder according to any one of claims 8 to 12.

Citation Information

Patent Citations

  • High electric resistance magnetic material and its production

    JP1997111421A

  • Composite magnetic material

    JP2003243215A

  • Method of manufacturing dust core and dust core

    JP2009117484A

  • Powder for dust core and dust core, and method of manufacturing the same

    JP2010251600A

  • Soft magnetic powder dust core, reactor, choke coil, stator and motor using the same, and method for producing soft magnetic powder dust core

    JP2013171967A